Discourse and organizational change - Grant, David, 1964-; Michelson, Grant; Oswick, Cliff; Wailes, Nick (Journal of organizational change management ;, 2005)
This e-book is the second of two devoted to the topic of discourse and organizational change. The two e-books reflect a growing interest among researchers in examining the organizational discourse(s) that may be used to describe, analyse, theorise and enact the processes and practices that constitute organizational change. This turn to discourse is, the Guest Editors suggest, driven by a growing disillusionment with more mainstream theories and approaches to the study of change.